2022
DOI: 10.1002/jia2.25889
|View full text |Cite
|
Sign up to set email alerts
|

Men missing from the HIV care continuum in sub‐Saharan Africa: a meta‐analysis and meta‐synthesis

Abstract: Introduction:Men are missing along the HIV care continuum. However, the estimated proportions of men in sub-Saharan Africa meeting the UNAIDS 95-95-95 goals vary substantially between studies. We sought to estimate proportions of men meeting each of the 95-95-95 goals across studies in sub-Saharan Africa, describe heterogeneity, and summarize qualitative evidence on factors influencing care engagement. Methods: We systematically searched PubMed and Embase for peer-reviewed articles published between 1 January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 212 publications
(499 reference statements)
0
34
0
Order By: Relevance
“…Gender disparities are pervasive throughout the HIV care continuum in sub-Saharan Africa. Compared with women, men test, receive treatment, and achieve viral suppression at lower rates; have higher mortality rates; and have greater loss to follow up after testing and treatment [1][2][3][4][5][6][7]. Studies conducted in multiple sites throughout sub-Saharan Africa have shown that men's access to HIV-related services at healthcare clinics is adversely affected by multiple factors, including stigma, privacy and confidentiality concerns, long queues, financial barriers, and fear of testing positive [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Gender disparities are pervasive throughout the HIV care continuum in sub-Saharan Africa. Compared with women, men test, receive treatment, and achieve viral suppression at lower rates; have higher mortality rates; and have greater loss to follow up after testing and treatment [1][2][3][4][5][6][7]. Studies conducted in multiple sites throughout sub-Saharan Africa have shown that men's access to HIV-related services at healthcare clinics is adversely affected by multiple factors, including stigma, privacy and confidentiality concerns, long queues, financial barriers, and fear of testing positive [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…This did not emerge as an explicitly stated theme in our data, however the implicit identification of health facilities as the domain of women and children may partially explain the importance of positive facility experiences for promoting men’s engagement in ART services [ 31 ]. Client-centered care, waiting spaces that encourage discussion and socialization among clients, and male-tailored services could enhance positive experiences at facilities; these positive experiences may increase men’s attendance at HIV services [ 3 , 31 ]. Given that many patients feel healthy at the time of diagnosis, friendly interactions at ART clinics (either with facility staff or fellow clients) may be one of the few immediate benefits associated with early ART initiation [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar trend was seen with overall self-reported health, although this was not statistically significant. The unequal benefit of HIV care programs on well-being in the region is well known, with men being less likely to access HIV care and remain in care than with women, resulting in a widening mortality gap between the sexes Bor et al, 2015;Tsai & Siedner, 2015;Nardell et al, 2022). These differences have resulted in different life expectancy gains by gender among PWH in the region Johnson et al, 2013;Mills et al, 2011).…”
Section: Discussionmentioning
confidence: 99%